Advent and implications of cryosurgery in maxillofacial mucosal lesions - Pathumai Murugadoss; Guru Prasad Thulasidoss; Gnanam Andavan; Raja Krishna Kumar (Wolters Kluwer Medknow Publications, 2016)
Cryosurgery is the application of cold to the diseased tissue and their destruction. It is an economical and safe method used for the treatment of mucosal lesions. It is well tolerated by patients of all age groups. This paper presents a review on the mechanism of cell death following cryosurgery and its implications in oral mucosal lesions.